Effect of Awareness Programme on Knowledge and Practice Regarding Birth Preparedness and Complication Readiness among Pregnant Women at Panchla Block, Howrah District - Reba Sarkar; Smritikana Mani (Indonesian Journal of Global Health Research, 2020)
Birth preparedness and complication readiness or BP/ CR of pregnant women enable maternal and newborn survival. A quasi-experimental study was conducted to know the effect of awareness programme on knowledge and practice regarding BP/ CR among pregnant women in Panchla Block, Howrah District , West Bengal. Using the Mother and Child tracking system register 72 mothers with gestational age ≥ 36 weeks selected randomly from 12 sub-centers. Intervention was done through individual and group instructions and data were collected before and after intervention. The intervention through awareness programme to the pregnant women significantly raised the awareness level regarding BP/ CR, as the mean score was higher in the intervention group regarding birth preparedness ((17.1 after intervention versus 13.5 before intervention, t value 12.73 with 35 df , p<0.05) and complication readiness (13.8 after intervention versus 6.1 before intervention, t value 25.31 with 35 df , p<0.05). However, there is no significant improvement in mean score in the control group regarding birth preparedness. There is also, strong positive association between knowledge and practice (chi-square value 16.99 with 1 df and p<0.01). Keyword: birth preparedness; complication readiness